IMPLEMENTASI AKUNTANSI KEUANGAN BERBASIS SAK ETAP DALAM PENYUSUNAN LAPORAN KEUANGAN AGEN BRILINK : STUDI KASUS PADA CV. TIGA PERMATA - Mochamad Fatchur Rohman; Rievca, Savira (Ekomania, 2023)
Financial statements have a function as a tool to regulate the management between income and expenses, analyze financial performance that can provide information related to financial position, to research profit or loss, and others that are used and manage finances so that they are used regularly. The purpose of this research is to find out how to apply and understand the accounting recording method for micro-entrepreneurs Agent Brilink CV. Tiga Permata and whether it is in accordance with the standards set by the government. FSA EWPA was established with the aim of facilitating entities without public accountability such as business in one accounting period. Agent Brilink CV. Tiga Permata was chosen as the research sample using convenience sampling method with qualitative descriptive analysis method. The results of this study indicate that the understanding of the staff and employees regarding the Financial Accounting Standards for Entities Without Public Accountability (FSA EWPA) is still very simple, due to the lack of knowledge of the staff and employees regarding the technical aspects of preparing financial statements based on FSA EWPA. The Brilink CV Tiga Permata agent feels that a financial report showing cash out, in and profit and loss is sufficient